Amyloid arthropathy in smoldering myeloma: Do not take it lightly. (2021) - Muchtar, Eli; King, Rebecca L.; McPhail, Ellen D.; Thorpe, Matthew P.; Gonsalves, Wilson; Ernste, Floranne; Grogan, Martha; Dispenzieri, Angela; Gertz, Morie A.
Abstract: We report a case of smoldering multiple myeloma patient who developed signs and symptoms consistent with polyarthritis. A PET-CT demonstrated marked FDG activity in multiple joints, concerning for inflammatory arthritis. Arthrocentesis from the glenohumeral joint was consistent with inflammatory synovial fluid with no evidence for infection or crystals. Congo-red stain of the synovial fluid was positive, and mass-spectrometry based amyloid typing was consistent with wild-type transthyretin type. The patient responded instantly to glucocorticoids. This case reports highlights the feasibility of non-tissue diagnosis of amyloidosis using body fluids and underscores the importance of accurate typing to avoid erroneous treatment